Northern religions and shamanism - Hoppál, Mihály; Pentikäinen, Juha; International Association for the History of Religions (Budapest : Akadémiai Kiadó ; Helsinki : Finnish Literature Society, 1992)
Religies en sjamanisme in het hoge Noorden.
"The regional conference of the International Association of [sic] the History of Religions"--P. [v].
Includes bibliographical references and index.
Keywords: Arctic peoples -- Folklore -- Congresses; Arctic peoples -- Religion -- Congresses; Shamanism -- Congresses; Uralic peoples -- Folklore -- Congresses; Uralic peoples -- Religion -- Congresses; Uralic philology -- Congresses